The New ADE-TLM Algorithm for Modeling Debye Medium - El ouardy, El hadi; El Faylali, Hanan (International Journal of Electrical and Computer Engineering Systems, 2023)
In this paper, we present a novel approach to simulating the interaction between electromagnetic waves and a Debye medium utilizing a Transmission Line Matrix (TLM) algorithm with the symmetrical condensed node (SCN-TLM) technique. The proposed method utilizes the polarization current within the media and incorporates the auxiliary differential equation (ADE) technique to handle scattering following the conventional discretization process. The averaged approximation is employed to utilize the polarization current density J and the electric voltage. By reducing the number of operations required per iteration, the New ADE- TLM method has successfully decreased the computational time compared to time convolution techniques. Despite this reduction in computational time, the New ADE-TLM method maintains a numerical accuracy that is comparable to that of time convolution techniques. The efficiency and precision of this approach are confirmed by the agreement between the results obtained and those predicted by the analytic model.